High-strength corrosion-resistant unsaturated polyester resin and preparation method thereof
By optimizing the binary acid distribution ratio and an appropriate amount, an anhydrodiasis is added, and the lack of unsaturated polyester resin in terms of thermal deformation, chemical resistance and water absorption rate is solved. High -performance resin.
Patent Information
- Application Number
- CN202411511124.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-24
AI Technical Summary
The existing unsaturated polyester resins have shortcomings in thermal deformation, chemical resistance and water absorption, and dibasic acid ratio and compatibility problems lead to poor crystallinity and mechanical properties of the resin.
By optimizing the binary acid ratio, adding an anhydride of the dehuminyl acid in an appropriate amount, improve the crystalline problem of the unsaturated resin of the benzene, improve the compatibility of the resin to the crosslinker, and prepare a high -strength corrosion -resistant unsaturated polyester resin Essence
The prepared high -strength corrosion -resistant and unsaturated polyester resin has high strength, high -heat deformation temperature, high water resistance and high corrosiveness, which solves the lack of traditional resin in these areas.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of unsaturated polyester resins, and in particular relates to a high-strength corrosion-resistant unsaturated polyester resin and a preparation method thereof. Background Art
[0002] Unsaturated polyester resin is often used as a base material for pultrusion, FRP manufacturing, and pipeline repair. The properties of the unsaturated polyester resin matrix determine the material's heat resistance, water resistance, chemical resistance, and toughness.
[0003] Traditional unsaturated polyester resins generally contain a large amount of diethylene glycol, which leads to a large number of ether bonds in the unsaturated polyester resin. Due to the particularity of the ether bonds themselves, such as instability when heated and the ability to react with water to produce hydrogen bonds, this directly leads to a decrease in the heat resistance and chemical resistance of the unsaturated polyester resin, and also greatly increases the water absorption rate of the resin.
[0004] Terephthalic acid can significantly improve the heat deformation temperature and chemical resistance of resins in the existing synthesis technology, but due to its symmetrical structure, the terephthalic acid product used in large quantities has poor compatibility with styrene and is easy to form crystals; isophthalic acid has low solubility, less volatility when heated, and the resulting resin has high mechanical properties and water resistance, but its price is relatively high, and using it alone increases production costs; phthalic anhydride introduces benzene rings into the polyester molecular chain, which can reduce the crystallinity of the resin, but its temperature resistance is poor when used alone; since the electron cloud distribution of phthalic anhydride is extremely asymmetric and its chemical stability is poor, the unsaturated polyester resin has poor chemical corrosion resistance. Summary of the invention
[0005] The technical problem to be solved by the present invention is: to overcome the deficiencies of the prior art and provide a high-strength corrosion-resistant unsaturated polyester resin and a preparation method thereof; the present invention can improve the crystallinity problem of terephthalic unsaturated resin and enhance the compatibility of the resin with a cross-linking agent by optimizing the dibasic acid ratio and adding an appropriate amount of phthalic anhydride; the prepared high-strength corrosion-resistant unsaturated polyester resin has high strength, high heat deformation temperature, high water resistance and high corrosion resistance.
[0006] The technical solution adopted by the present invention to solve the technical problem is as follows: the high-strength corrosion-resistant unsaturated polyester resin comprises the following components by mass percentage: 4-5% isophthalic acid, 6.5-8% terephthalic acid, 7.5-8.4% phthalic anhydride, 18-18.5% maleic anhydride, 19-20% diethylene glycol, 0.007-0.015% catalyst, 0.02-0.03% antioxidant, 9.5-10.5% propylene glycol, 0.018-0.025% inhibitor, 0.015-0.03% paraffin wax, and 31.7-32.94% cross-linking agent; The mass ratio of terephthalic acid to isophthalic acid is (1.3-2.0):1, and the mass ratio of phthalic anhydride to isophthalic acid is (1.6-2.05):1.
[0007] Isophthalic acid has low solubility, less volatility when heated, and the resulting resin has high mechanical properties and water resistance; terephthalic acid can significantly increase the heat deformation temperature and chemical resistance of the resin, but due to its symmetrical structure, the terephthalic acid product has poor compatibility with styrene and is easy to form crystals; phthalic anhydride can reduce the heat deformation temperature of the resin, and an appropriate amount of phthalic anhydride can improve the compatibility of the resin with the cross-linking agent; optimizing the ratio of multiple dibasic acids can improve the crystallinity problem of terephthalic resin, and the prepared high-strength and corrosion-resistant unsaturated polyester resin has high strength, high heat deformation temperature, high water resistance and high corrosion resistance.
[0008] The catalyst is monobutyltin oxide, zinc acetate or stannous chloride; the catalyst can accelerate the chemical reaction rate and improve production efficiency. Monobutyltin oxide can withstand high temperature reactions of 250°C, is suitable for esterification and condensation reactions, and is neutral and non-corrosive, ensuring its application safety in high temperature and corrosive environments; zinc acetate has high chemical stability and safety; stannous chloride has a high density and low vapor pressure at room temperature, is relatively stable during storage and transportation, and is not easy to volatilize.
[0009] The antioxidant is 2,6-di-tert-butyl or triphenyl phosphite; the antioxidant can protect the resin material from or delay oxidation, improve the stability and service life of the resin material, and ensure that the resin material can maintain good performance under various environmental conditions; 2,6-di-tert-butyl is a high-performance antioxidant with the advantages of good oil solubility, great adaptability, and high antioxidant efficiency; triphenyl phosphite, as a phosphite antioxidant, has the characteristics of good compatibility, high phosphorus content, good thermal stability, and high antioxidant efficiency.
[0010] The polymerization inhibitor is one or more of hydroquinone, p-benzoquinone, p-tert-butylcatechol, and o-methyl hydroquinone in any proportion. The polymerization inhibitor improves the storage stability of the resin and extends its service life by preventing or reducing the curing reaction, delaying the self-condensation process, and adjusting the polymerization reaction rate, thereby ensuring the quality and performance of the resin. Hydroquinone is a commonly used polymerization inhibitor, and its advantages include low price, good effect at room temperature, good storage stability, and good solubility in organic solvents, so it is widely used; p-benzoquinone can still work under anaerobic conditions, is suitable for etherification processes protected by nitrogen or other inert gases, and still has a good polymerization inhibition effect at high temperatures, which makes p-benzoquinone an ideal choice for the production of highly active unsaturated polyester resins; p-tert-butylcatechol, as a high-efficiency polymerization inhibitor, has an important position in industrial production and scientific research due to its excellent polymerization inhibition efficiency and wide application fields; o-methyl hydroquinone has good storage stability and can give the resin good storage stability.
[0011] The paraffin wax is 54# fully refined paraffin wax or 58# fully refined paraffin wax. Paraffin wax is mainly used as a lubricant to improve processing efficiency, prevent and overcome adhesion, and improve smoothness and glossiness. Compared with other types of paraffin wax, 54# and 58# fully refined paraffin waxes have lower oil content, which reduces the problems caused by high oil content. After the refining process, 54# and 58# fully refined paraffin waxes contain almost no impurities, ensuring the purity and quality of the high-strength and corrosion-resistant unsaturated polyester resin. 54# and 58# fully refined paraffin waxes have good chemical stability, can maintain their physical and chemical properties unchanged under various environments, and also have good plasticity, which can adapt to different molding requirements.
[0012] The cross-linking agent is styrene or methyl styrene, which is both a cross-linking agent and a diluent, and can improve the processing performance of the material by adjusting the viscosity to ensure the smooth progress of the process; by adding an appropriate amount of diluent, the cost can be reduced without sacrificing the material performance; the smaller the degree of polymerization of the cross-linking agent between the cross-linking points of styrene or methyl styrene, the greater the cross-linking density, the lower the elasticity of the unsaturated polyester, and the better the heat resistance.
[0013] According to another aspect of the present invention, there is also provided a method for preparing a high-strength corrosion-resistant unsaturated polyester resin, the method comprising the following steps: (1) Under nitrogen protection, terephthalic acid, isophthalic acid, diethylene glycol, a catalyst and an antioxidant are added to a reaction vessel, and the esterification reaction is carried out at 210-220°C until the reaction vessel becomes uniform and transparent, and the temperature is lowered; (2) Cool the reaction vessel to 120-160°C, add propylene glycol, maleic anhydride, phthalic anhydride and polymerization inhibitor; heat to 150-165°C and keep warm for 0.5-1.5h, heat to 200-210°C for the second time to carry out polycondensation reaction, and dehydrate when the acid value in the reaction vessel reaches 42-48mgKOH / g; (3) The reaction vessel is cooled to 170-190°C, and an inhibitor and paraffin are added; the reaction vessel is cooled to 100-120°C, and a diluent is added and mixed evenly to obtain a high-strength, corrosion-resistant unsaturated polyester resin.
[0014] The reason for carrying out the reaction under nitrogen protection is to prevent the reactants from contacting with oxygen and avoid the occurrence of oxidation reactions. It also helps to reduce side reactions and improve the selectivity and yield of the reaction.
[0015] When the reaction vessel in step (1) is uniform and transparent, the acid value is reduced to 10-12 mgKOH / g. In the esterification reaction, the acid value is an important indicator, which reflects the content of free carboxyl groups in the reactants. After the free carboxyl groups in the reactants undergo esterification reaction with alcohol, the acid value will gradually decrease, indicating that the reaction is in progress. When the acid value reaches 10-12 mgKOH / g, it means that most of the carboxyl groups have participated in the reaction and the corresponding esters have been generated. At this time, the reaction system has reached a uniform and transparent state, indicating that the reaction is close to completion and the product quality is high.
[0016] The secondary heating rate in step (2) is 12-15°C / h, and the polycondensation reaction time is 2-3h. The temperature is raised to 150-165°C and the holding time is 0.5-1.5h. During the holding stage, a large number of by-products are generated during the reaction and discharged with nitrogen. The secondary heating rate is 12-15°C / h. Direct heating or too fast heating will cause a large loss of raw materials, affecting the subsequent polycondensation product indicators, resulting in a high acid value or high viscosity, which in turn affects product performance. The temperature is raised to 200-210°C for polycondensation reaction, and the reaction time is 2-3h. The temperature range of 200-210°C is conducive to the solution polycondensation reaction, can promote chemical reactions between monomers, and avoid the problem of instability in the molten state. The reaction time of 2-3h can ensure that the monomers are fully polycondensed in sufficient time to form a polymer compound. The phthalic anhydride can adjust the unsaturation of the polyester molecules, improve the crystallinity problem of the high-strength corrosion-resistant unsaturated polyester resin, and improve the compatibility of the high-strength corrosion-resistant unsaturated polyester resin with the cross-linking agent. The high-strength corrosion-resistant unsaturated polyester resin obtained after the polycondensation reaction has a higher molecular weight.
[0017] The dehydration in step (2) is vacuum dehydration, and the vacuum dehydration is performed until the acid value reaches 20 to 30 mgKOH / g; the purpose of vacuum dehydration is to remove the water generated during the reaction to promote the reaction to form a polymer; when the vacuum dehydration is performed until the acid value reaches 20 to 30 mgKOH / g, it indicates that the water in the reaction system has been basically removed and the polycondensation reaction between the reactants is basically completed; when the vacuum dehydration is performed until the acid value reaches 20 to 30 mgKOH / g, the high-strength corrosion-resistant unsaturated polyester resin finally prepared has a higher molecular weight; when the vacuum dehydration is performed until the acid value is greater than 30 mgKOH / g, the high-strength corrosion-resistant unsaturated polyester finally prepared The molecular weight of the resin is relatively low, and the tensile strength and flexural strength will decrease; when vacuum dehydration is performed until the acid value is lower than 20 mgKOH / g, the viscosity of the polyester increases faster and faster, the acid value decreases slower and slower, and the molecular weight growth is not obvious. To meet the index requirements, more cross-linking agents need to be added. The increase in the proportion of cross-linking agents in the resin will also reduce the performance of the resin. Adding more cross-linking agents will also increase production costs. From an economic point of view, the acid value should be controlled above 20 mgKOH / g; combined with the above content, it can be seen that when vacuum dehydration is performed until the acid value reaches 20-30 mgKOH / g, the prepared high-strength corrosion-resistant unsaturated polyester resin has a higher molecular weight and lower cost.
[0018] The chemical reaction formula involved in the synthesis process step (1) → step (3) of the present invention is: The chemical reaction formula of step (1) is: ① , ② , ③ ; The chemical reaction formula of step (2) is: ④ , ⑤ , ⑥ .
[0019] In the chemical reaction formula of step (1), R 1 -CH2-CH2-O-CH2-CH2-, R 3 for , R 4 for , respectively represent the groups in diethylene glycol, terephthalic acid and isophthalic acid except the active end groups; diethylene glycol, terephthalic acid and isophthalic acid generate esters through reactions ① and ②, and the reaction products have hydroxyl and carboxyl groups at both ends, and continue to react ③ to obtain long-chain molecules.
[0020] In the chemical reaction formula of step (2), R 1-CH2-CH2-O-CH2-CH2-, R 2 for , R 3 for , R 4 for , R 5 for , R 6 -CH=CH-, respectively representing the groups other than the active end groups in diethylene glycol, propylene glycol, terephthalic acid, isophthalic acid, phthalic anhydride and maleic anhydride; the molecular chain of the reaction product of step (1) contains an ester bond, and the molecular chain of the product of diethylene glycol, propylene glycol, phthalic anhydride and maleic anhydride after reactions ④ and ⑤ contains an ester bond and an unsaturated double bond, and the reaction product has hydroxyl and carboxyl groups at both ends, and continues to react ⑥ to form a chain molecule with a variety of different chain segments.
[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention can improve the crystallinity problem of terephthalic unsaturated resin and enhance the compatibility of resin with crosslinking agent by optimizing the ratio of dibasic acid and adding an appropriate amount of phthalic anhydride; the prepared high-strength and corrosion-resistant unsaturated polyester resin has high strength, high heat deformation temperature, high water resistance and high corrosion resistance.
[0022] (2) In the preparation method of the present invention, vacuum dehydration is performed until the acid value reaches 20 to 30 mgKOH / g, so that the high-strength corrosion-resistant unsaturated polyester resin finally prepared has a higher molecular weight, thereby having higher tensile strength and flexural strength. DETAILED DESCRIPTION
[0023] Embodiment 3 is the best embodiment of the present invention. The present invention will be further described below in conjunction with specific embodiments and comparative examples.
[0024] Terephthalic acid: industrial grade, Jinan Xiangfeng Weiye Chemical Co., Ltd.; Isophthalic acid: industrial grade, Jinan Huijinchuan Trading Co., Ltd.; Phthalic anhydride: industrial grade, Jinan Angxin Chemical Co., Ltd.; Maleic anhydride: industrial grade, Jinan Shuangying Chemical Co., Ltd.; Monobutyltin oxide: industrial grade, Shandong Wangtong Chemical Co., Ltd.; Zinc acetate: industrial grade, Jinan Zhiheng Zhiyuan Chemical Technology Co., Ltd.; Stannous chloride: industrial grade, Jinan Yucai Chemical Co., Ltd.; 2,6-di-tert-butyl triphenyl phosphite: industrial grade, Jinan Feiyue Chemical Co., Ltd.; hydroquinone: industrial grade, Shandong Yukang Chemical Co., Ltd.; p-Benzoquinone: industrial grade, Jinan Xichuan Chemical Technology Co., Ltd.; p-tert-butylcatechol: industrial grade, Jinan Xuchen Chemical Technology Co., Ltd.; o-methylhydroquinone: industrial grade, Weifang Aidi Chemical Co., Ltd.; 54# fully refined paraffin: industrial grade, Wuhan Xindongyi Chemical Co., Ltd.; 58# fully refined paraffin: industrial grade, Wuhan Xindongyi Chemical Co., Ltd.; Styrene: industrial grade, Shandong Jinli Chemical Co., Ltd.; Methyl styrene: industrial grade, Shandong Jinghao Chemical Co., Ltd.
[0025] Example 1 Preparation method of high-strength corrosion-resistant unsaturated polyester resin: (1) Under nitrogen protection, 80 parts of terephthalic acid, 40 parts of isophthalic acid, 196 parts of diethylene glycol, 0.11 parts of monobutyltin oxide and 0.24 parts of triphenyl phosphite were added to a reaction vessel, and an esterification reaction was carried out at 215° C. When the acid value in the container was reduced to 11 mgKOH / g and the temperature was lowered, the reaction was continued until the container was uniform and transparent; (2) The reaction vessel was cooled to 140°C, and 99 parts of propylene glycol, 182 parts of maleic anhydride, 75 parts of phthalic anhydride and 0.12 parts of hydroquinone were added; the temperature was raised to 160°C and kept for 1 hour, and the secondary heating rate was 13°C / h, and the temperature was raised to 205°C for polycondensation reaction for 2.5 hours; when the acid value in the reaction vessel reached 45 mgKOH / g, vacuum dehydration was performed until the acid value reached 25 mgKOH / g; (3) The reaction vessel was cooled to 180°C, and 0.1 parts of o-methyl hydroquinone and 0.23 parts of 58# fully refined paraffin were added; the reaction vessel was cooled to 110°C, and 327.2 parts of styrene were added and mixed evenly to obtain a high-strength, corrosion-resistant unsaturated polyester resin.
[0026] Example 2 Preparation method of high-strength corrosion-resistant unsaturated polyester resin: (1) Under nitrogen protection, 66 parts of terephthalic acid, 45 parts of isophthalic acid, 196 parts of diethylene glycol, 0.11 parts of monobutyltin oxide and 0.24 parts of triphenyl phosphite were added to a reaction vessel, and an esterification reaction was carried out at 215° C. When the acid value in the container was reduced to 11 mgKOH / g and the temperature was lowered, the reaction was continued until the container was uniform and transparent; (2) The reaction vessel was cooled to 140°C, and 99 parts of propylene glycol, 182 parts of maleic anhydride, 84 parts of phthalic anhydride and 0.12 parts of hydroquinone were added; the temperature was raised to 160°C and kept for 1 hour, and the secondary heating rate was 13°C / h, and the temperature was raised to 205°C for polycondensation reaction for 2.5 hours; when the acid value in the reaction vessel reached 45 mgKOH / g, vacuum dehydration was performed until the acid value reached 25 mgKOH / g; (3) The reaction vessel was cooled to 180°C, and 0.1 parts of o-methyl hydroquinone and 0.23 parts of 58# fully refined paraffin were added; the reaction vessel was cooled to 110°C, and 327.2 parts of styrene were added and mixed evenly to obtain a high-strength, corrosion-resistant unsaturated polyester resin.
[0027] Example 3 Preparation method of high-strength corrosion-resistant unsaturated polyester resin: (1) Under nitrogen protection, 71 parts of terephthalic acid, 42 parts of isophthalic acid, 196 parts of diethylene glycol, 0.11 parts of monobutyltin oxide and 0.24 parts of triphenyl phosphite were added to a reaction vessel, and an esterification reaction was carried out at 215° C. When the acid value in the container was reduced to 11 mgKOH / g and the temperature was lowered, the reaction was continued until the container was uniform and transparent; (2) The reaction vessel was cooled to 140°C, and 99 parts of propylene glycol, 182 parts of maleic anhydride, 82 parts of phthalic anhydride and 0.12 parts of hydroquinone were added; the temperature was raised to 160°C and kept for 1 hour, and the secondary heating rate was 13°C / h, and the temperature was raised to 205°C for polycondensation reaction for 2.5 hours; when the acid value in the reaction vessel reached 45 mgKOH / g, vacuum dehydration was performed until the acid value reached 25 mgKOH / g; (3) The reaction vessel was cooled to 180°C, and 0.1 parts of o-methyl hydroquinone and 0.23 parts of 58# fully refined paraffin were added; the reaction vessel was cooled to 110°C, and 327.2 parts of styrene were added and mixed evenly to obtain a high-strength, corrosion-resistant unsaturated polyester resin.
[0028] Example 4 Preparation method of high-strength corrosion-resistant unsaturated polyester resin: (1) Under nitrogen protection, 65 parts of terephthalic acid, 50 parts of isophthalic acid, 200 parts of diethylene glycol, 0.07 parts of monobutyltin oxide and 0.2 parts of triphenyl phosphite were added to a reaction vessel, and the esterification reaction was carried out at 215° C. When the temperature in the vessel was uniform and transparent and the acid value was reduced to 11 mgKOH / g, the temperature was lowered; (2) The reaction vessel was cooled to 140°C, and 95 parts of propylene glycol, 180 parts of maleic anhydride, 80 parts of phthalic anhydride and 0.08 parts of hydroquinone were added; the temperature was raised to 160°C and kept for 1 hour, and the secondary heating rate was 13°C / h, and the temperature was raised to 205°C for polycondensation reaction for 2.5 hours; when the acid value in the reaction vessel reached 45 mgKOH / g, vacuum dehydration was performed until the acid value reached 25 mgKOH / g; (3) The reaction vessel was cooled to 180°C, and 0.1 parts of o-methyl hydroquinone and 0.15 parts of 58# fully refined paraffin were added; the reaction vessel was cooled to 110°C, and 329.4 parts of styrene were added and mixed evenly to obtain a high-strength, corrosion-resistant unsaturated polyester resin.
[0029] Example 5 Preparation method of high-strength corrosion-resistant unsaturated polyester resin: (1) Under nitrogen protection, 80 parts of terephthalic acid, 40 parts of isophthalic acid, 190 parts of diethylene glycol, 0.15 parts of monobutyltin oxide and 0.3 parts of triphenyl phosphite were added to a reaction vessel, and the esterification reaction was carried out at 215° C. When the acid value in the container was reduced to 11 mgKOH / g and the temperature was lowered, the reaction was continued until the container was uniform and transparent; (2) The reaction vessel was cooled to 140°C, and 105 parts of propylene glycol, 185 parts of maleic anhydride, 82 parts of phthalic anhydride and 0.13 parts of hydroquinone were added; the temperature was raised to 160°C and kept for 1 hour, and the secondary heating rate was 13°C / h, and the temperature was raised to 205°C for polycondensation reaction for 2.5 hours; when the acid value in the reaction vessel reached 45 mgKOH / g, vacuum dehydration was performed until the acid value reached 25 mgKOH / g; (3) The reaction vessel was cooled to 180°C, and 0.12 parts of o-methyl hydroquinone and 0.3 parts of 58# fully refined paraffin were added; the reaction vessel was cooled to 110°C, and 317 parts of styrene were added and mixed evenly to obtain a high-strength, corrosion-resistant unsaturated polyester resin.
[0030] Example 6 Preparation method of high-strength corrosion-resistant unsaturated polyester resin: (1) Under nitrogen protection, 71 parts of terephthalic acid, 42 parts of isophthalic acid, 196 parts of diethylene glycol, 0.11 parts of zinc acetate and 0.24 parts of 2,6-di-tert-butyl are added to a reaction vessel, and an esterification reaction is carried out at 215° C. When the acid value in the container is uniform and transparent and the acid value is reduced to 11 mgKOH / g, the temperature is lowered; (2) The reaction vessel was cooled to 140°C, and 99 parts of propylene glycol, 182 parts of maleic anhydride, 82 parts of phthalic anhydride and 0.12 parts of p-benzoquinone were added; the temperature was raised to 160°C and kept for 1 hour, and the secondary heating rate was 13°C / h, and the temperature was raised to 205°C for polycondensation reaction for 2.5 hours; when the acid value in the reaction vessel reached 45 mgKOH / g, vacuum dehydration was performed until the acid value reached 25 mgKOH / g; (3) The reaction vessel was cooled to 180°C, and 0.1 parts of p-benzoquinone and 0.23 parts of 54# fully refined paraffin were added; the reaction vessel was cooled to 110°C, and 327.2 parts of styrene were added and mixed evenly to obtain a high-strength, corrosion-resistant unsaturated polyester resin.
[0031] Example 7 Preparation method of high-strength corrosion-resistant unsaturated polyester resin: (1) Under nitrogen protection, 71 parts of terephthalic acid, 42 parts of isophthalic acid, 196 parts of diethylene glycol, 0.11 parts of stannous chloride and 0.24 parts of triphenyl phosphite were added to a reaction vessel, and the esterification reaction was carried out at 215° C. When the acid value in the container was reduced to 11 mgKOH / g and the temperature was lowered, the reaction was continued until the container was uniform and transparent; (2) The reaction vessel was cooled to 140°C, and 99 parts of propylene glycol, 182 parts of maleic anhydride, 82 parts of phthalic anhydride and 0.12 parts of p-tert-butylcatechol were added; the temperature was raised to 160°C and kept for 1 hour, and the secondary heating rate was 13°C / h, and the temperature was raised to 205°C for polycondensation reaction for 2.5 hours; when the acid value in the reaction vessel reached 45 mgKOH / g, vacuum dehydration was performed until the acid value reached 25 mgKOH / g; (3) The reaction vessel was cooled to 180°C, and 0.1 parts of p-tert-butylcatechol and 0.23 parts of 58# fully refined paraffin were added; the reaction vessel was cooled to 110°C, and 327.2 parts of styrene were added and mixed evenly to obtain a high-strength, corrosion-resistant unsaturated polyester resin.
[0032] Example 8 Preparation method of high-strength corrosion-resistant unsaturated polyester resin: (1) Under nitrogen protection, 71 parts of terephthalic acid, 42 parts of isophthalic acid, 196 parts of diethylene glycol, 0.11 parts of monobutyltin oxide and 0.24 parts of triphenyl phosphite were added to a reaction vessel, and an esterification reaction was carried out at 210° C. When the acid value in the container was reduced to 10 mgKOH / g and the temperature was lowered, the reaction was continued until the container was uniform and transparent; (2) The reaction vessel was cooled to 140°C, and 99 parts of propylene glycol, 182 parts of maleic anhydride, 82 parts of phthalic anhydride and 0.12 parts of hydroquinone were added; the temperature was raised to 150°C and kept for 0.5 h, and the secondary heating rate was 12°C / h, and the temperature was raised to 200°C for polycondensation reaction for 3 h; when the acid value in the reaction vessel reached 48 mgKOH / g, vacuum dehydration was performed until the acid value reached 25 mgKOH / g; (3) The reaction vessel was cooled to 170°C, and 0.1 parts of o-methyl hydroquinone and 0.23 parts of 58# fully refined paraffin were added; the reaction vessel was cooled to 100°C, and 327.2 parts of styrene were added and mixed evenly to obtain a high-strength, corrosion-resistant unsaturated polyester resin.
[0033] Example 9 Preparation method of high-strength corrosion-resistant unsaturated polyester resin: (1) Under nitrogen protection, 71 parts of terephthalic acid, 42 parts of isophthalic acid, 196 parts of diethylene glycol, 0.11 parts of monobutyltin oxide and 0.24 parts of triphenyl phosphite were added to a reaction vessel, and an esterification reaction was carried out at 210° C. When the acid value in the container was reduced to 12 mgKOH / g and the temperature was lowered, the reaction was continued until the container was uniform and transparent; (2) The reaction vessel was cooled to 160°C, and 99 parts of propylene glycol, 182 parts of maleic anhydride, 82 parts of phthalic anhydride and 0.12 parts of hydroquinone were added; the temperature was raised to 165°C and kept for 1.5 hours, and the secondary heating rate was 15°C / h, and the temperature was raised to 210°C for polycondensation reaction for 2 hours; when the acid value in the reaction vessel reached 42 mgKOH / g, vacuum dehydration was performed until the acid value reached 25 mgKOH / g; (3) The reaction vessel was cooled to 190°C, and 0.1 parts of o-methyl hydroquinone and 0.23 parts of 58# fully refined paraffin were added; the reaction vessel was cooled to 120°C, and 327.2 parts of styrene were added and mixed evenly to obtain a high-strength, corrosion-resistant unsaturated polyester resin.
[0034] Example 10 Preparation method of high-strength corrosion-resistant unsaturated polyester resin: (1) Under nitrogen protection, 71 parts of terephthalic acid, 42 parts of isophthalic acid, 196 parts of diethylene glycol, 0.11 parts of monobutyltin oxide and 0.24 parts of triphenyl phosphite were added to a reaction vessel, and an esterification reaction was carried out at 215° C. When the acid value in the container was reduced to 11 mgKOH / g and the temperature was lowered, the reaction was continued until the container was uniform and transparent; (2) The reaction vessel was cooled to 140°C, and 99 parts of propylene glycol, 182 parts of maleic anhydride, 82 parts of phthalic anhydride and 0.12 parts of hydroquinone were added; the temperature was raised to 160°C and kept for 1 hour, and the secondary heating rate was 13°C / h, and the temperature was raised to 205°C for polycondensation reaction for 2.5 hours; when the acid value in the reaction vessel reached 45 mgKOH / g, vacuum dehydration was performed until the acid value reached 20 mgKOH / g; (3) The reaction vessel was cooled to 180°C, and 0.1 parts of o-methyl hydroquinone and 0.23 parts of 58# fully refined paraffin were added; the reaction vessel was cooled to 110°C, and 327.2 parts of styrene were added and mixed evenly to obtain a high-strength, corrosion-resistant unsaturated polyester resin.
[0035] Embodiment 11 Preparation method of high-strength corrosion-resistant unsaturated polyester resin: (1) Under nitrogen protection, 71 parts of terephthalic acid, 42 parts of isophthalic acid, 196 parts of diethylene glycol, 0.11 parts of monobutyltin oxide and 0.24 parts of triphenyl phosphite were added to a reaction vessel, and an esterification reaction was carried out at 215° C. When the acid value in the container was reduced to 11 mgKOH / g and the temperature was lowered, the reaction was continued until the container was uniform and transparent; (2) The reaction vessel was cooled to 140°C, and 99 parts of propylene glycol, 182 parts of maleic anhydride, 82 parts of phthalic anhydride and 0.12 parts of hydroquinone were added; the temperature was raised to 160°C and kept for 1 hour, and the secondary heating rate was 13°C / h, and the temperature was raised to 205°C for polycondensation reaction for 2.5 hours; when the acid value in the reaction vessel reached 45 mgKOH / g, vacuum dehydration was performed until the acid value reached 30 mgKOH / g; (3) The reaction vessel was cooled to 180°C, and 0.1 parts of o-methyl hydroquinone and 0.23 parts of 58# fully refined paraffin were added; the reaction vessel was cooled to 110°C, and 327.2 parts of styrene were added and mixed evenly to obtain a high-strength, corrosion-resistant unsaturated polyester resin.
[0036] Comparative Example 1 The preparation method of the high-strength corrosion-resistant unsaturated polyester resin described in this comparative example is the same as that of Example 3, except that in step (1), 113 parts of terephthalic acid and 0 parts of isophthalic acid are used.
[0037] Comparative Example 2 The method for preparing the high-strength corrosion-resistant unsaturated polyester resin described in this comparative example is the same as that in Example 3, except that in step (1), 0 parts of terephthalic acid and 113 parts of isophthalic acid are used.
[0038] Comparative Example 3 The preparation method of the high-strength corrosion-resistant unsaturated polyester resin described in this comparative example is the same as that in Example 3, except that in step (1), 161 parts of terephthalic acid and 41 parts of isophthalic acid are used; in step (2), 0 parts of phthalic anhydride are used; and in step (3), 323 parts of styrene are used.
[0039] Comparative Example 4 The method for preparing the high-strength corrosion-resistant unsaturated polyester resin described in this comparative example is the same as that in Example 3, except that in step (2), vacuum dehydration is performed until the acid value reaches 40 mgKOH / g.
[0040] Performance Testing The performance of the high-strength and corrosion-resistant unsaturated polyester resins prepared in the examples and comparative examples was tested. The specific test results are shown in Table 1.
[0041] The tensile strength of high-strength and corrosion-resistant unsaturated polyester resin is tested with reference to GB / T2567-2021 "Test method for properties of resin castings".
[0042] The tensile elastic modulus of high-strength and corrosion-resistant unsaturated polyester resin is tested in accordance with GB / T2567-2021 "Test method for properties of resin castings".
[0043] The elongation at break of high-strength and corrosion-resistant unsaturated polyester resin is tested in accordance with GB / T2567-2021 "Test method for properties of resin castings".
[0044] The flexural strength of high-strength and corrosion-resistant unsaturated polyester resin is tested with reference to GB / T2567-2021 "Test method for properties of resin castings".
[0045] The flexural elastic modulus of high-strength and corrosion-resistant unsaturated polyester resin is tested in accordance with GB / T2567-2021 "Test method for properties of resin castings".
[0046] The impact strength of high-strength and corrosion-resistant unsaturated polyester resin is tested with reference to GB / T2567-2021 "Test method for properties of resin castings".
[0047] The Barcol hardness of high-strength and corrosion-resistant unsaturated polyester resin is tested with reference to GB / T3854-2017 "Barcol hardness test method for reinforced plastics".
[0048] The heat deformation temperature test standard of high-strength and corrosion-resistant unsaturated polyester resin is tested in accordance with GB / T1643-2019 "Plastic Bending Load Heat Deformation Temperature".
[0049] The water resistance of high-strength and corrosion-resistant unsaturated polyester resin is tested in accordance with GB / T2567-2021 "Test method for aging properties of glass fiber reinforced plastics".
[0050] The chemical corrosion resistance of high-strength corrosion-resistant unsaturated polyester resin is tested in accordance with GB / T3857-2017 "Test method for chemical resistance of glass fiber reinforced thermosetting plastics".
[0051] The mass of high-strength and corrosion-resistant unsaturated polyester resin before and after corrosion was weighed using analytical balance FA2004B.
[0052] Table 1 Performance data of high strength corrosion resistant unsaturated polyester resin in embodiments and comparative examples .
[0053] As shown in Table 1, by optimizing the ratio of dibasic acid, the high-strength corrosion-resistant unsaturated polyester resin prepared in Example 3 has the highest heat deformation temperature, tensile strength, bending strength and Barcol hardness, high water resistance, and the best corrosion resistance. The tensile strength, bending strength, heat deformation temperature and Barcol hardness of other examples are slightly worse than those of Example 3, but still have excellent water resistance, and the corrosion resistance is also significantly better than that of Comparative Examples 1 to 3, and the various mechanical properties are good.
[0054] Comparative Example 1 does not add isophthalic acid, and the prepared high-strength corrosion-resistant unsaturated polyester resin is easy to become turbid, has a high water absorption rate, and has poor corrosion resistance; Comparative Example 2 does not add terephthalic acid, and the prepared high-strength corrosion-resistant unsaturated polyester resin has moderate strength, but the lowest heat deformation temperature, and the water absorption rate is improved compared with Comparative Example 1, but the water absorption rate does not reach the effect of Examples 1 to 3, and its corrosion resistance is also significantly weaker than that of Examples 1 to 3; Comparative Example 3 does not add phthalic acid, and the prepared high-strength corrosion-resistant unsaturated polyester resin has a heat deformation temperature that reaches the level of Example 1, but the sample is also easy to become turbid, and the water absorption rate and corrosion resistance are similar to those of Comparative Example 2, and do not reach the effect of Examples 1 to 3. Comparative Example 4 vacuum dehydration until the acid value reaches 40 mgKOH / g, the prepared high-strength corrosion-resistant unsaturated polyester resin has a low molecular weight, and the tensile strength and bending strength will decrease; vacuum dehydration until the acid value reaches 20 to 30 mgKOH / g, the high-strength corrosion-resistant unsaturated polyester resin finally prepared has a high molecular weight and low cost.
[0055] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A high-strength, corrosion-resistant unsaturated polyester resin, characterized in that: In terms of mass percentage, it contains the following ingredients: 4-5% isophthalic acid, 6.5-8% terephthalic acid, 7.5-8.4% phthalic anhydride, 18-18.5% maleic anhydride, 19-20% diethylene glycol, 0.007-0.015% catalyst, 0.02-0.03% antioxidant, 9.5-10.5% propylene glycol, 0.018-0.025% inhibitor, 0.015-0.03% paraffin wax, and 31.7-32.94% cross-linking agent; The mass ratio of terephthalic acid to isophthalic acid is (1.3-2.0):1, and the mass ratio of phthalic anhydride to isophthalic acid is (1.6-2.05):
1.
2. The high-strength, corrosion-resistant unsaturated polyester resin according to claim 1, characterized in that: The catalyst is monobutyltin oxide, zinc acetate or stannous chloride.
3. The high-strength, corrosion-resistant unsaturated polyester resin according to claim 1, characterized in that: The antioxidant is 2,6-di-tert-butyl or triphenyl phosphite.
4. The high-strength, corrosion-resistant unsaturated polyester resin according to claim 1, characterized in that: The polymerization inhibitor is one or a combination of any proportion of hydroquinone, p-benzoquinone, p-tert-butylcatechol, and o-methylhydroquinone.
5. The high-strength, corrosion-resistant unsaturated polyester resin according to claim 1, characterized in that: The paraffin wax is 54# fully refined paraffin wax or 58# fully refined paraffin wax.
6. The high-strength, corrosion-resistant unsaturated polyester resin according to claim 1, characterized in that: The diluent is styrene or methylstyrene.
7. A method for preparing the high-strength corrosion-resistant unsaturated polyester resin according to claims 1 to 6, characterized in that: The method comprises the following steps: (1) Under nitrogen protection, terephthalic acid, isophthalic acid, diethylene glycol, a catalyst and an antioxidant are added to a reaction vessel, and the esterification reaction is carried out at 210-220°C until the reaction vessel becomes uniform and transparent, and the temperature is lowered; (2) Cool the reaction vessel to 120-160°C, add propylene glycol, maleic anhydride, phthalic anhydride and polymerization inhibitor; heat to 150-165°C and keep warm for 0.5-1.5h, heat to 200-210°C for the second time to carry out polycondensation reaction, and dehydrate when the acid value in the reaction vessel reaches 42-48mgKOH / g; (3) The reaction vessel is cooled to 170-190°C, and an inhibitor and paraffin are added; the reaction vessel is cooled to 100-120°C, and a diluent is added and mixed evenly to obtain a high-strength, corrosion-resistant unsaturated polyester resin.
8. The method for preparing a high-strength corrosion-resistant unsaturated polyester resin according to claim 7, characterized in that: When the reaction vessel in step (1) is uniform and transparent, the acid value is reduced to 10-12 mgKOH / g.
9. The method for preparing a high-strength corrosion-resistant unsaturated polyester resin according to claim 7, characterized in that: The secondary heating rate in step (2) is 12-15°C / h, and the polycondensation reaction time is 2-3h.
10. The method for preparing a high-strength corrosion-resistant unsaturated polyester resin according to claim 7, characterized in that: The dehydration in step (2) is vacuum dehydration, and the vacuum dehydration is carried out until the acid value reaches 20 to 30 mgKOH / g.
Citation Information
Cited By
Unsaturated polyester resin for imitation jade handicrafts and preparation method of unsaturated polyester resin
CN120504786A